PEMANFAATAN MEDIA BERBASIS ICT “KAHOOT” DALAM PEMBELAJARAN PPKN UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA - Andarusni Alfansyur; Mariyani Mariyani (Bhineka Tunggal Ika: Kajian Teori dan Praktik Pendidikan PKn, 2019)
Abstract: The effective learning is learning centered to the students. This is because students are the centered of learning. The involvement of students in learning is important to provide student’s experience. Some effort to involve students in learning is to provide a learning media. The appropriate learning media must certainly be adapted to the needs of the students in the class. The learning which was conducted at MAN 3 Palembang is based on the result of the analysis of the needs and the materials that the students showed are more enthusiasm if it is use a media. One of the appropriate media is ICT-based which can be easily accessed by students is ICT-based. Kahoot is one of ICT-based media, because it depends network and device. Kahoot can increase students’ motivation because it is multimedia and give challenges to the students. The purpose of this study is to determine the use of kahoot media in learning PPKn to increase student motivation in MAN 3 Palembang. The research method of this study is library research. The discussion of this study are the important of accuracy in the selection of instructional media, kahoot as ICT-based media, efforts to increase students’ motivation and utilization of kahoot media in PPKn learning to increase students’ motivation. Key words: ICT-Based Media, Kahoot, Students’ Motivation